Antimicrobial effect and physicochemical properties of an adhesive system containing nanocapsules. Issue 6 (June 2017) - Genari, Bruna; Leitune, Vicente Castelo Branco; Jornada, Denise Soledade; Camassola, Melissa; Arthur, Rodrigo Alex; Pohlmann, Adriana Raffin; Guterres, Silvia Stanisçuaski; Collares, Fabrício Mezzomo; Samuel, Susana Maria Werner
Highlights: Triclosan and indomethacin-loaded nanocapsules were successfully incorporated into adhesive system without compromising to be used for conservative treatment. Drug delivery nanotechnology improves the efficacy of drugs and consequently health care. It represents a promising field of study in adhesive dentistry. The study is the first step toward the goal of providing fillers for adhesive systems to act as antimicrobial and inflammatory agent with continuous action. Abstract: Objective: To incorporate indomethacin and triclosan-loaded nanocapsules into primer and adhesive, and evaluate its properties. Methods: Indomethacin and triclosan were encapsulated by deposition of preformed polymer and subsequently characterized regarding morphology, particle size, drug content and cytotoxicity. Nanocapsules (NCs) were incorporated into primer at 2% and into adhesive at 1, 2, 5, and 10% concentrations. Degree of conversion (DC) and softening in ethanol of the adhesive were evaluated. Drug release and drug diffusion through dentin was quantified by high performance liquid chromatography. Antimicrobial test was performed until 96 h. Results: Spherical and biocompatible NCs presented mean size of 159 nm. Drugs content was 3 mg indomethacin/g powder and 2 mg triclosan/g powder. Incorporating NCs in adhesive showed no influence in DC (p = 0.335). The addition of 2% of NCs showed no influence in softening in ethanol (p > 0.05). After 120 h, 93% of indomethacin and 80% of triclosan were released from primer, 20% of indomethacin and 17% of triclosan were released from adhesive with 10% of NCs. Indomethacin showed diffusion through dentin. In 24 h, adhesive containing 2 and 5% of NCs using primer with NCs showed antimicrobial effect. In 96 h, adhesives containing different concentration of NCs promoted antimicrobial effect. Conclusions: Indomethacin and triclosan-loaded nanocapsules were successfully incorporated into primer and adhesive, promoting controlled drugs release, indomethacin diffusion through dentin and antimicrobial effect without compromising its physicochemical properties. Significance: Indomethacin and triclosan-loaded nanocapsules have potential to prevent recurrent caries and to be used in deep cavities controlling pulpar inflammatory process.